2017
DOI: 10.1002/jcla.22260
|View full text |Cite
|
Sign up to set email alerts
|

Application of molecular, microbiological, and immunological tests for the diagnosis of bone and joint tuberculosis

Abstract: Xpert MTB/RIF, IGRA, TNF-α, and TGF-βs expression have value in the rapid diagnosis of bone and joint tuberculosis, and the sensitivity and accuracy of bone and joint tuberculosis diagnosis by combining them can improve it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In the patients with NIH IIIb, the PSEP cut-off of 1.00 ng/mL corresponds to a detection sensitivity of 69% and a specificity of 70%, suggesting that PSEP as a clinical test for CP has operability and good clinical value. In addition, previous studies have suggested that TNF-α, as a multifunctional cytokine, is involved in the pathogenesis of various diseases [32] . PSEP is only reported in prostate diseases and has excellent specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients with NIH IIIb, the PSEP cut-off of 1.00 ng/mL corresponds to a detection sensitivity of 69% and a specificity of 70%, suggesting that PSEP as a clinical test for CP has operability and good clinical value. In addition, previous studies have suggested that TNF-α, as a multifunctional cytokine, is involved in the pathogenesis of various diseases [32] . PSEP is only reported in prostate diseases and has excellent specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is a major infectious disease that mainly affects lung tissue, but may also infect other organs. The infection can be spread by two major routes: hematogenous or lymphatic [12].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of BJTB, just like that of other forms of EPTB, is very challenging, due to its paucibacillary nature [48]. The delayed diagnosis and treatment of BJTB can lead to serious complications, such as joint destruction, contractures in large joints, growth arrest, and neurological impairment in spinal tuberculosis, resulting in long-term morbidity and disability [36]. Invasive examination is a necessary diagnostic step in most cases.…”
Section: Discussionmentioning
confidence: 99%